A molecular phylogeny of the harriers (Circus, Accipitridae) indicate the role of long distance dispersal and migration in diversification - Oatley, Graeme; Simmons, Robert E; Fuchs, Jérôme (Molecular phylogenetics and evolution, 2015)
The monophyly of the raptorial Circus genus (harriers) has never been in question, but the specific status of many, often vulnerable island endemic, taxa remains uncertain. Here we utilise one mitochondrial and three nuclear loci from all currently recognised Circus taxa (species and subspecies) to infer a robust phylogeny, to estimate the divergence date and to reconstruct the biogeographic origins of the Circus group. Our phylogeny supports both the monophyly of Circus and polyphyly of the genus Accipiter. Depending on the rate of molecular clock used, the emergence of the harrier clade took place between 4.9 and 12.2mya which coincides with the worldwide formation of open habitats which extant harriers now exploit. The sister relationship of the Northern Harrier C. cyaneus hudsonius and the Cinereous Harrier C. cinereus contradicts previous classifications that treated the former as conspecific with the Hen Harrier C. cyaneus cyaneus. Thus both should be elevated to species status: C. hudsonius and C. cyaneus. Further, the African Marsh C. ranivorus and the European Marsh C. aeruginosus Harriers emerge as sister species. The remaining marsh harriers exhibit very little genetic diversity, and are all recently diverged taxa that exhibit allopatric distributions. Considering their sister relationship and geographic proximity, we recommend treating C. approximans and C. spilonotus spilothorax as subspecies of C. approximans. For C. spilonotus spilonotus C. maillardi maillardi and C. maillardi macrosceles, their plumage and morphometric differences, phylogenetic relationship and geographic distributions make lumping of these taxa as a single species complicated. We thus propose to recognise as separate, recently evolved species: C. spilonotus, C. maillardi and C. macrosceles. Biogeographic inferences on the ancestral origin of harriers are uncertain, indicating that the harriers emerged in either the Neotropics, Palearctic or Australasia. We are, however, able to show that speciation within the harriers was driven by long range dispersal and migration events.
Keywords: Phylogenetics; Models, Genetic; Sequence Analysis, DNA; modely genetické; biologická evoluce; Australasia; ekosystém; Falconiformes; Bayes Theorem; Circus; rozšíření zvířat; genetická variace; Biological Evolution; DNA, Mitochondrial; pravděpodobnostní funkce; Bayesova věta; Biogeographic history; Genetic Variation; Accipitridae; zvířata; mitochondriální DNA; fylogeneze; Migration; Animal Distribution; sekvenční analýza DNA; Ecosystem; Australasie; Phylogeny; Likelihood Functions; Animals